Direct and inverse simulation applied to the identification and quantification of point pollution sources in rivers. (October 2022) - Lugão, Bruno C.; Knupp, Diego C.; Rodriges, Pedro Paulo G.W.
Abstract: Concerns about water resource availability and preservation have grown over recent decades due to increased levels of pollution stemming mainly from economic activities and uncontrolled population growth. In this context, the present study seeks to identify and quantify point pollution sources released from river margins. A two-dimensional transient advection–diffusion equation is proposed to model the physical problem, while the inverse problem, for the identification and quantification of pollution sources, is investigated through the definition of an objective function, considering or not the availability of prior information. The objective function then is minimized by applying the differential evolution algorithm. Simulated cases are presented and discussed for distinct release scenarios, including single and multiple point locations. The results obtained were found to be satisfactory even for the most difficult cases, illustrating that the computational approaches presented in this work may yield valuable tools in the management of surface water resources. Highlights: Pollutant dispersion is modeled and release sources are estimated. The modeling of spills that occur at the margins of watercourses is addressed. Point spills are estimated with measurements from a single monitoring site. Valuable information of load and location of multi-point releases are retrieved.